Dexamethasone-Loaded Ureasil Hydrophobic Membrane for Bone Guided Regeneration - Barros, Rafaella Moreno; Silva, Camila Garcia da [UNESP]; Costa, Kammila Martins Nicolau; Silva Junior, Arnóbio A. da; Scardueli, Cássio Rocha [UNESP]; Marcantonio, Rosemary Adriana Chiérici [UNESP]; Chiavacci, Leila Aparecida [UNESP]; Oshiro Junior, João Augusto (MDPI, 2022)
Physical barrier membranes have been used to release active substances to treat critical bone defects; however, hydrophilic membranes do not present a prolonged release capacity. In this sense, hydrophobic membranes have been tested. Thus, this study aimed to develop hydrophobic membranes based on mixtures of ureasil–polyether-type materials containing incorporated dexamethasone (DMA) for the application in guided bone regeneration. The physicochemical characterization and biological assays were carried out using small-angle X-ray scattering (SAXS), an in vitro DMA release study, atomic force microscopy (AFM), a hemolysis test, and in vivo bone formation. The swelling degree, SAXS, and release results revealed that the u-PPO400/2000 membrane in the proportion of 70:30 showed swelling (4.69% ± 0.22) similar to the proportions 90:10 and 80:20, and lower than the proportion 60:40 (6.38% ± 0.49); however, an equal release percentage after 134 h was observed between the proportions 70:30 and 60:40. All u-PPO materials presented hemocompatibility (hemolysis ≤2.8%). AFM results showed that the treatments with or without DMA did not present significant differences, revealing a flat/smooth surface, with no pores and/or crystalline precipitates. Finally, in vivo results revealed that for both the commercial hydrophilic membrane and u-PPO400/2000 (70:30) after 60 days, the bone formation volume was 21%. In conclusion, hybrid membranes present unique characteristics for treating critical bone defects, considering the delayed and prolonged release results associated with the physical barrier capacity.
Keywords: critical bone defect size; hydrophobic membrane; organic–inorganic hybrid materials